Sámi Musical Performance and the Politics of Indigeneity in Northern Europe - Hilder, Thomas (Rowman & Littlefield Publishers, 2014)
The Sámi are Europe’s only recognized indigenous people living across regions of Norway, Sweden, Finland and the Russian Kola peninsula. The subjects of a history of Christianization, land dispossession, and cultural assimilation, the Sámi have through their self-organization since World War II worked towards Sámi political self-determination across the Nordic states and helped forge a global indigenous community. Accompanying this process was the emergence of a Sámi music scene, in which the revival of the distinct and formerly suppressed unaccompanied vocal tradition of joik was central. Through joiking with instrumental accompaniment, incorporating joik into forms of popular music, performing on stage and releasing recordings, Sámi musicians have played a key role in articulating a Sámi identity, strengthening Sámi languages, and reviving a nature-based cosmology. Thomas Hilder offers the first book-length study of this diverse and dynamic music scene and its intersection with the politics of indigeneity. Based on extensive ethnographic research, Hilder provides portraits of numerous Sámi musicians, studies the significance of Sámi festivals, analyzes the emergence of a Sámi recording industry, and examines musical projects and cultural institutions that have sought to strengthen the transmission of Sámi music. Through his engaging narrative, Hilder discusses a wide range of issues—revival, sovereignty, time, environment, repatriation and cosmopolitanism—to highlight the myriad ways in which Sámi musical performance helps shape notions of national belonging, transnational activism, and processes of democracy in the Nordic peninsula. Sámi Musical Performance and the Politics of Indigeneity in Northern Europe will not only appeal to enthusiasts of Nordic music, but, by drawing on current interdisciplinary debates, will also speak to a wider audience interested in the interplay of music and politics. Unearthing the challenges, contradictions and potentials presented by international indigenous politics, Hilder demonstrates the significance of this unique musical scene for the wider cultural and political transformations in twenty-first-century Europe and global modernity.